Vita Bulla. Overvejelser om en gravsten i Sorø Kirke - Holm, Knud (Hikuin, 2012)
Vita Bulla. Thoughts concerning a tombstone from Soroe Church By Knud Holm The article describes a tombstone laid over a five-dayold boy back in 1632. It can be seen in the church – the old monastery church – in Soer or Soroe in the western part of Zealand (Sjælland in Danish). The stone, which is in Øland limestone and 107 x 53 cm in size, bears a circular relief showing a boy blowing soap bubbles as an allegorical symbol of the extreme brevity of life experienced in this case. The boy, Jacob, was the son of the couple Wichmann Hasebart and Maren Brod, and he was their firstborn child. They were married the year before. The family only lived in Soroe for a few years. The father had been appointed tutor to Prince Valdemar Christian, son of King Christian IV and Kirsten Munk. The prince, then about 11 years old, besides the tutoring by Hasebart, attended the school in Soroe, the »Soroe Academy«, where boys, primarily of the nobility, were taught. A possible model for the boy depicted in the relief might well have been the engraving in the illustration, made by Hendrick Goltzius, the Dutch artist (1558-1617). Other Vanitas symbols are incorporated in this engraving. The large skull is obvious, but along with the soap bubbles we also see the flower and the smoke, both symbols immediately readable at the time by the educated – and further elaborated on in the verse lines below the picture. This has served as an invitation to seek examples of the use not only of the bubbles but also of some of the other symbols on tombstones and sepulchral tablets from the 16th to the 19th century. A single literary allusion to the flower/death connection is mentioned in Madame Sabran’s poem to her daughter, 1794. The bubble motif is also exemplified in the painting by Karel Dujardin from the 17th century showing the boy standing on a shell in the sea. While Goltzius shows the boy and the skull, Dujardin reverses the sequence, so to speak, and refers to the birth of the boy? – then the bubble. After the article was completed, a few further examples of the boy blowing soap-bubbles found in Danish churches were added. The tombstone from Ubby Church is unusual, since four Vanitas symbols are shown on shields at the corners of the stone – a place normally occupied by the four evangelists or their symbols, or in some cases rosettes or even shields with the arms of the deceased nobleman. To the more common Vanitas symbols a peculiar addition is the unusual variant of the ‘hourglass symbol’ that occurs on some 16th and 17th century tombstones – in the form of references to mechanical clocks – either the face of a clock or a foliot (a sort of balance used to regulate the running of the clock, before the introduction of the pendulum by Huygens in about 1660).